Backstabbing for beginners [videorecording (DVD)] - Fly, Per, 1960-; James, Theo, 1984-; Kingsley, Ben, 1943-; Bisset, Jacqueline, 1944-; Soussan, Michael (A24 Films, 2018)
Based on a true story, this gripping and timely thriller follows an idealistic UN employee as he investigates the grisly murder of his predecessor and uncovers a vast global conspiracy that may even involve his own boss.